US Degree Qualifications Profile: A catalyst for transparency, quality and permeability? : Reflections on a work in progress - Rein, Volker [Verfasser] (My University, 2011)
"Education and training stakeholders worldwide in government, business and practice try to address challenges of quality and labour market needs by qualifications frameworks. US education politics on postsecondary education currently focuses on measures to promote institution and program accountability and to increase degree and credential completion in order to address the relevant labour market demands for an advanced skilled workforce. The US Lumina Foundation has developed a draft for Degree Qualifications Profile (DQP) in 2011 with references to the European Bologna Qualifications Framework for higher education to address these targets by the shift to learning outcomes and competencies. The challenge for the DQP is whether and how this instrument can bridge academic and occupational requirements and facilitate the conversion of non-credit to credit-bearing learning in terms of permeability." (Autorenreferat, BIBB-Doku)
Keywords: Höhere Berufsbildung; Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Lernergebnisorientierung; USA